THE INFLUENCE OF SLEEVE GASTRECTOMY ON HEMOSTASIS IN PATIENTS WITH MORBID OBESITY - A. S. Murodov; O. R. Teshaev; A. R. Mavlyanov (Journals Park Publishing, 2024)
Evaluation of hemostasis disorders in patients with morbid obesity and study of the significance of the practice of longitudinal resection of the stomach. From 2019 to 2022 years in our clinic were performed 231 metabolic and bariatric surgeries, including 82 minigastric bypasses (MGS) and 149 sleeve gastrectomy (SG). Over the years, SG was performed in 149 patients with different body mass index. 84 (56,3%) patients suffering from morbid obesity had grade III obesity, 65 (43,7%) had grade II obesity. The analyzes performed showed that patients suffering from morbid obesity have a tendency to hypercoagulability in vascular-platelet and coagulation hemostasis. In morbid obesity, depending on its severity, statistically significant disturbances in the value of hemostasis parameters of patients were observed, a moderate positive association with BMI was revealed; genetic predisposition, as well as in patients with concomitant diseases such as diabetes mellitus.
Keywords: Bariatric surgery, morbid obesity, hemostasis parameters, sleeve gastrectomy.